Mounting dengue awareness: A cost effective Strategy for prevention - Srivastava, Kajal; Sharma, Parul; Rathod, Hetal; Ghonge, Swati; Bhawalkar, Jitendra Shamsunder; Vyas, Shaili (Indian Journal of Community Health, 2015)
Background: Dengue is a serious illness which takes toll on human health every year. The best way to prevent it is by increasing awareness among common people. This study was conducted to assess the level of knowledge, attitudes and practices regarding dengue fever in people urban heath training centre in Pune, Maharashtra. Methods: A cross-sectional study was conducted among patients attending OPD of Urban heath training centre of department of community medicine, Pune situated in Ajmera, Pimpri, Pune. Through convenience sampling, a questionnaire was administered to patients after taking their informed consent. Results: A total of 100 patients were interviewed. Among knowledge 83% had heard about dengue and the most common source of information was TV & radio (72.3%) Most of them were aware regarding mosquito bite being the mode of dengue transmission (80.7%). 22% were unaware regarding biting time of mosquito while 22% said night is the biting time of dengue mosquito. 62.7% were using coils for mosquito bite prevention followed by mosquito net (43.4%) and spray (31.3%.). Conclusion: This study revealed that most of the study population is aware of dengue illness and increasing education level is having positive attitude on dengue illness.